Cutting-edge therapies in the treatment of surgical wounds - Zepeda, Jose M.; Contreras, Javier; Osuna, Felix; Jimenez, Melany; Murrieta, Alejandro (International Surgery Journal, 2021)
Wounds are inherent to being alive and also a reminder of our fragility in the face of the hostilities of this planet. Annually, it is estimated that 4511 operations are performed per 100,000 population, or 1 surgical procedure every year for every 22 people. There is an art to treating wounds. The support by the doctor for wound healing favors the early recovery of this, in addition to minimizing the risk of infection and gives an aesthetically pleasing appearance, the care that is used today ranging from the cleaning of the wound, the approximation of the edges thanks to the sutures, etc. The following is a review of cutting-edge therapies in this area of medicine, such as biotechnologies, growth factors, gene therapy, and stem cells. Projections indicate an increasing decrease in morbidity and mortality associated with surgical wounds and their repair, as well as more favorable cosmetic outcomes for patients. The results showed that all the described techniques, although not perfect, are perfectible, and with the pertinent precautions can be maximized in favor of care. There is the possibility in the near future, to be a basic part of wound care, in terms of protocols of care, but also in the individualization of treatment.